Stress eating and sleep disturbance as mediators in the relationship between depression and obesity in low-income, minority women. Issue 3 (May 2016) - Yu, Jessica; Fei, Kezhen; Fox, Ashley; Negron, Rennie; Horowitz, Carol
Summary: The purpose of this study was to explore potential mediators of the relationship between depression and obesity in a sample of low-income, minority women. Data were extracted from a sample of 535 women enrolled in a weight loss intervention for the prevention of type 2 diabetes. Using a non-parametric bootstrapping procedure, the potential mediation effects of stress eating and sleep disturbance on the relationship between depression and obesity were tested. Results of a single mediation model indicated that depressive symptomatology was significantly associated with obesity ( β = 0.800, SE = 0.290, p = 0.006), and that stress eating ( β = 0.166, 95% CI [0.046, 0.328]) and sleep disturbance ( β = 1.032, 95% CI [0.612, 1.427]) were significant independent mediators of this relationship. Sleep disturbance remained a significant mediator in a combined mediation model ( β = 1.009, 95% CI [0.653, 1.399]). Findings add to the growing literature on the psychosocial factors implicated in the link between depression and obesity, particularly among disadvantaged populations. Future longitudinal research should aim to establish causal pathways between obesity, stress eating, sleep disturbance, and depression.